BETWEEN UNITY AND DIVERSITY: Resketching the Relation between Institutional-Affiliated Indonesian Muslim Intellectuals and the Government (1990-2001) (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
This article describes the relation between institutional-affiliated Muslim intellectuals and the government in Indonesia during the period of 1990-2001. By analyzing the interview data and documentary studies, it tries to resketch the historical context of social and institutional relation of Muslim intellectuals. This article finds that pluralism is a notion which can be used to sociologically describe the diversity of Indonesian Muslim intellectuals, occasionally leading them, both with and without an institutional association, to different difficulties to unite each other. It maintains that the way Muslim Intellectuals appear to be close to, or distant from, the government depends heavily on who becomes the president or who is in the centre of power. They tend to be close to the government if the president comes out of their social affiliation. The opposite goes the other way around. The fact that unity and diversity exist in Indonesian Islamic organizations and institutions, it suggests, just follows the need and the demand of their members.